ChemInform Abstract: Peroxides as "Switches" of Dialkyl H‐Phosphonate: Two Mild and Metal‐Free Methods for Preparation of 2‐Acylbenzothiazoles and Dialkyl Benzothiazol‐2‐ylphosphonates. Issue 10 (March 2015) - Chen, Xiao‐Lan; et al., et al.
Abstract The presented peroxide mediated procedures give access to a wide variety of two kinds of benzothiazoles.